(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to enhance the productivity and professionalism of Taekwondo Valentino Club management through digital technology adoption. The program addressed administrative and communication processes that were still manual, creating inefficiencies, limited transparency, and poor accessibility. A participatory approach was applied, actively involving partners in socialization, digital literacy training, system implementation, mentoring, and program handover. The results showed significant improvements. The management aspect score increased from 2.34 to 4.46 (+90.6%), while the social aspect rose from 2.44 to 4.50 (+84.4%), both statistically significant at p < 0.05. These outcomes reflect substantial gains in administrative efficiency, transparency, and data accuracy. Beyond management, the program strengthened human resource capacity, enhanced community engagement, and improved club visibility through digital media. Overall, the initiative demonstrates that website-based information systems can sustainably transform sports club governance. It also supports SDGs points 4 and 9 and aligns with the Merdeka Belajar Kampus Merdeka (MBKM) policy by involving students in technology development and community mentoring.